Health Module Intervention of Physical Activity (PA) in Controlling Blood Sugar Levels of People With Type 2 Diabetes Mellitus - kamriana; Salmah Arafah; suardi; wahyudin; ratnasari Iskandar; zain, Zainuddin; Adi sadli (International Journal of Nursing and Health Services (IJNHS), 2022)
Background: Physical activity is a part of exercise, considered the cornerstone in treating type 2 diabetes. Physical activity controls blood glucose directly circulating and increases tissue sensitivity to insulin, reduces the risk of cardiovascular disease, and reduces mortality. Objective: This study aims to determine the difference in changes in blood sugar given through the Physical Activity Health Module (PA) media. Design: This study used pre-experimental using two groups of pre-test and post-test. The sample is 100 people who have DMT2 in Takalar Regency. The research results show a significant difference between the provision of education through the health module media to changes in blood sugar. Conclusion: Giving the Physical Activity (PA) health module can reduce blood sugar levels in patients with Diabetes Mellitus type. Recommendation: The Physical Activity Health (PA) module is the evidence base to assist decision-makers, especially for nurses holding the Diabetes Mellitus program, in making relevant policies. It is also essential to design effective promotion and prevention programs to improve health services, especially promoting physical activity programs for DMT2 patients